2021
DOI: 10.3389/fneur.2021.668880
|View full text |Cite
|
Sign up to set email alerts
|

What Tinnitus Therapy Outcome Measures Are Important for Patients?– A Discrete Choice Experiment

Abstract: Introduction: The therapeutic rationale varies among tinnitus therapies. A recent study identified which outcome measures should be used for different types of interventions. What patients consider the most important outcome measure in tinnitus therapy is unclear.Objectives: To study the preference of the tinnitus patient for different outcome measures in tinnitus therapy.Methods: A discrete choice experiment was conducted. Participants were provided with two alternatives per choice set (nine choice sets total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…In summary, the effects of the combined treatment are stronger for the tinnitus loudness than for tinnitus distress, which is probably in favor for the tinnitus sufferers since a recent analysis by Rademaker et al 2021 [22] concluded that tinnitus patients consider loudness the most important outcome measure. With this study, we can only document the changes of tinnitus loudness and distress but cannot identify the underlying therapeutic mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…In summary, the effects of the combined treatment are stronger for the tinnitus loudness than for tinnitus distress, which is probably in favor for the tinnitus sufferers since a recent analysis by Rademaker et al 2021 [22] concluded that tinnitus patients consider loudness the most important outcome measure. With this study, we can only document the changes of tinnitus loudness and distress but cannot identify the underlying therapeutic mechanism.…”
Section: Discussionmentioning
confidence: 96%
“…In summary, the effects of the combined treatment are stronger for the tinnitus loudness than for tinnitus distress, which is probably in favor for the tinnitus sufferers since a recent analysis by Rademaker et al 2021 [ 23 ] concluded that tinnitus patients consider loudness the most important outcome measure. With this study, we can only document the changes of tinnitus loudness and distress but cannot identify the underlying therapeutic mechanism.…”
Section: Discussionmentioning
confidence: 98%
“…The secondary outcome is the prediction model of the effect of electrical stimulation on tinnitus impact (or synonyms) measured by multi-item tinnitus questionnaires or single-item VAS scores of acceptance, annoyance, awareness, intrusiveness, unpleasantness 31 or loudness. 32 …”
Section: Methodsmentioning
confidence: 99%